The ichthyofauna and piscivorous avifauna in a small temporarily open/closed Eastern Cape estuary, South Africa - Blake, Justin David (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
The spatial and temporal patterns in selected components of the ichthyofauna and piscivorous avifauna in the small temporarily open/closed Riet River Estuary located on the eastern seaboard of southern Africa was investigated monthly over the period August 2005 to July 2006. The ichthyofauna within the littoral zone of the estuary was sampled using a 5 m seine net (8 stations) while a 30 m seine net (4 stations) was employed to sample the fish in the channel. Bird counts were made along repeat transects along the length of the estuary. Total ichthyofaunal abundances and biomass ranged between 1.60 and 8.67 individuals mâ »Â² and 0.45 to 21.76 g wwt mâ »Â² within the littoral zone, and between 0.08 and 0.44 individuals mâ »Â² and 0.58 and 36.52 g wwt mâ »Â² in the channel of the estuary. The highest values were generally recorded during the summer months. Results of the numerical analysis indicated that the breaching events recorded over the study period did not lead to a common trend in the ichthyofaunal community. In the absence of a link to the marine environment, the ichthyofaunal community in the littoral zone was numerically dominated by the estuarine resident species, Gilchristella aestuaria and to a lesser extent by Glossogobius callidus, which collectively accounted for ca. 54% of the total ichthyofauna sampled. The establishment of a link to the marine environment coincided with increased numbers of marine breeding species including Atherina breviceps and Rhabdosargus holubi to total fish counts within the estuary. Hierarchical cluster analysis did not identify any spatial patterns in the community structure of the ichthyofauna in the littoral zone or channel zone of the estuary, which could likely be linked to the absence of any distinct horizontal patterns in salinity and temperature within the system. A total of thirteen piscivorous bird species was recorded over the study period. Of the recorded species, six species were wading piscivores, four species were aerial divers and the remaining three species were pursuit swimmers. There were no significant correlations between the estimates of the ichthyofaunal abundance and biomass and bird numbers evident during the study (P> 0.05 in both cases). The Reed Cormorant (Phalacrocorax africanus) was the dominant species throughout the study, with a mean of 8.25 (SD Â± 7.90) individuals per count. Mean values of the Pied Kingfisher (Ceryle rudis) and Giant Kingfisher (Megaceryle maximus) were 3.42 (SD Â± 1.20) and 1.17 (SD Â± 0.60) individuals per count, respectively. The remaining species revealed mean values < 0.5 individuals per count. The highest bird numbers were recorded in winter reflecting the migration of large numbers of the Reed Cormorant into the system. Breaching events were associated with a decrease in total bird numbers, which was most likely due to loss of potential foraging habitat (littoral zone) for waders resulting from reduced water levels. Monthly food consumption by all piscivorous birds revealed large temporal variability, ranging from 26.35 to 140.58 kg per month. The observed variability could be linked to mouth phase and bird numbers.
Keywords: Estuarine fishes -- South Africa -- Eastern Cape; Bird populations -- South Africa -- Riet River Estuary; Estuaries -- South Africa -- Eastern Cape; Fish populations -- South Africa -- Riet River Estuary; Estuarine animals -- South Africa -- Riet River Estuary; Birds -- South Africa -- Riet River Estuary; Riet River Estuary (South Africa)